Cohort profile: the PERSIAN Dena Cohort Study (PDCS) of non-communicable diseases in Southwest Iran - Farahnaz Joukar; Javad Harooni; Reza Goujani; Masoumeh Khalighi Sikaroudi; Alireza Hatami; Mohammad-Amin Zolghadrpour; Mahdi Hejazi; Zahra Karimi; Fatemeh Rahmanpour; Sakineh Askari Shahid; Mohammad-Reza Jowshan (BMJ Open, 2024)
Purpose This study conducted in Dena County is a population-based cohort study as part of the Prospective Epidemiological Research Studies in Iran (PERSIAN). The specific objectives of this study were to estimate the prevalence of region-specific modifiable risk factors and their associations with the incidence of major non-communicable diseases (NCDs).Participants This PERSIAN Dena Cohort Study (PDCS) was conducted on 1561 men and 2069 women aged 35–70 years from October 2016 in Dena County, Kohgiluyeh and Boyer-Ahmad Province, Southwest Iran. The overall participation rate was 82.7%.Findings to date Out of 3630 participants, the mean age was 50.16 years, 2069 (56.9%) were women and 2092 (57.6%) were rural residents. Females exhibited higher prevalence rates of diabetes, hypertension, fatty liver, psychiatric disorders, thyroiditis, kidney stones, gallstones, rheumatic disease, chronic lung disease, depression and osteoporosis compared with males (p<0.05). Furthermore, the urban population showed elevated rates of diabetes, thyroiditis, kidney stones and epilepsy, whereas psychiatric disorders and lupus were more prevalent in rural areas (p<0.05). According to laboratory findings, 418 (13.0%), 1536 (48.1%) and 626 (19.3%) of the participants had fasting blood sugar >126 mg/dL, low-density lipoprotein >100 mg/dL and haematuria, respectively; most of them were female and urban people (p<0.05).Future plans PDCS will be planned to re-evaluate NCD-related incidence, all-cause and cause-specific mortality every 5 years, along with annual follow-up for 15 years. Some examples of additional planned studies are evaluation of genetic, environmental risk, spirometry and ECG tests.